Accuracy studies with carbon clusters at the Penning trap massspectrometer TRIGA-TRAP - Ketelaer, Jens; Beyer, Thomas; Blaum, Klaus; Block, M.; Eberhardt, K.; Eibach, Martin Andreas; Herfurth, F.; Smorra, Christian; Nagy, Sz. (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2010)
Extensive cross-reference measurements of well-known frequency ratios using various sizes of carbon cluster ions12Cn+ (10≤n≤23) were performed to determine the effects limiting the accuracy of mass measurements atthe Penning-trap facility TRIGA-TRAP. Two major contributions to the uncertainty of a mass measurement have been identified.Fluctuations of the magnetic field cause an uncertainty in the frequency ratio due to the required calibration by a referenceion of uf(νref)/νref = 6(2) × 10-11/min × Δt. A mass-dependent systematic shiftof the frequency ratio of epsilonm(r)/r = -2.2(2) × 10-9 × (m-mref)/uhas been found as well. Finally,the nuclide 197Au was used as a cross-check since its mass is already known with an uncertainty of 0.6 keV.